2000
DOI: 10.1046/j.1432-1327.2000.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Organization‐dependent effects of toxic bivalent ions

Abstract: The effects of bivalent ions on tubulin dynamics and the upper phase of glycolysis were investigated at different organization levels in vitro. Cu 21 , Cd 21 , Hg 21 and CrO 2± 4 inhibit the tubulin polymerization at an IC 50 of 14±24 mm with high cooperativity and also induce microtubule disassembly. The apparent binding constants of the ions to tubulin, estimated by fluorescence quenching, vary between 6 and 28 mm. BIAcore measurements for tubulin±tubulin interaction suggest that the presence of Cu 21 affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 27 publications
6
19
0
Order By: Relevance
“…Gold film chips (CM5) coated with carboxymethylated dextran were obtained from of 50 µL to reach room temperature and start polymerizing, we are confident that in our measurements mainly free tubulin dimers were present and not MTs since (using spectrophotometry and monitoring the absorption curve) we had previously determined that the characteristic time for our tubulin to polymerize into MTs was of the order of 45 minutes at room temperature (data not shown) agreeing with literature [26].…”
Section: Methodssupporting
confidence: 89%
“…Gold film chips (CM5) coated with carboxymethylated dextran were obtained from of 50 µL to reach room temperature and start polymerizing, we are confident that in our measurements mainly free tubulin dimers were present and not MTs since (using spectrophotometry and monitoring the absorption curve) we had previously determined that the characteristic time for our tubulin to polymerize into MTs was of the order of 45 minutes at room temperature (data not shown) agreeing with literature [26].…”
Section: Methodssupporting
confidence: 89%
“…Tubulins require post-translation folding, assembly into heterodimers, and then assembly into microtubules. In vitro and cell-based studies have shown that microtubules disassemble in excess copper (Liliom et al, 1999;Liliom et al, 2000;Nawaz et al, 2005;Pribyl et al, 2008;Liu et al, 2009). Copper might bind the sulfhydral groups of microtubules and thereby block microtubule assembly and/or induce disassembly (Wallin et al, 1977).…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%
“…Our SPR measurements took place at 24 o C and the time between injection and measurement was of the order of 10 s. Measurements were taken for times up to 5 minutes. Tubulin does not polymerize at 0 o C and although 10sec is adequate time for our sample of 50 µL to reach room temperature and start polymerizing, we are confident that in our measurements mainly free tubulin dimers were present and not MTs since (using spectrophotometry and monitoring the absorption curve) we had previously determined that the characteristic time for our tubulin to polymerize into MTs was of the order of 45 minutes at room temperature (data not shown) agreeing with literature [140].…”
Section: Tubulin and Immobilizationsupporting
confidence: 90%